О систематическом положении некоторых видов моногеней рода Paradiplozoon Achmerov, 1974 (Monogenea, Diplozoidae) - Хотеновский, И.А. (Вестник зоологии, 1981)
The studied collections and data from literature served as a basis for raising the Diplozoon paradoxum sapae R e i c h. - К 1., 1961 subspecies to the rank of a species, -with D. paradoxum ballerus K o m a r., 1964; D. bergi Gavr., 1964; D. balleri N ag., E rg ., P a s c h k e v ., 1970; D. sapa M ik a il., 1973 being its synonyms. The D. para- doxum bliccae R e ic h .-K I., 1961 subspecies is raised to the rank of a species with D. markewitschi В у ch., G у n L, Kov., 1964; D. gussevi G la s , G la s., 1964; D. per- sicum M ik a il.» 1973 being its synonyms. The both mentioned species are transferred to the Paradiplozoon genus. Descriptions are presented for the P. sapae R e ic h .-K I., 1961 and P. bliccae R e ic h .-K I., 1961 species.